2022
DOI: 10.1002/num.22898
|View full text |Cite
|
Sign up to set email alerts
|

Finite difference schemes for the fourth‐order parabolic equations with different boundary value conditions

Abstract: In this paper, the fourth-order parabolic equations with different boundary value conditions are studied. Six kinds of boundary value conditions are proposed. Several numerical differential formulae for the fourth-order derivative are established by the quartic interpolation polynomials and their truncation errors are given with the aid of the Taylor expansion with the integral remainders. Effective difference schemes are presented for the third Dirichlet boundary value problem, the first Neumann boundary valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(33 citation statements)
references
References 32 publications
1
32
0
Order By: Relevance
“…Example 1) H 1 semi-norm errors and convergence orders in space (𝜏 = 1/100,000). Lu et al[28] can also be observed. In addition, we can see that the fourth-order scheme (3.26)-(3.31) can reduce the storage and computational cost significantly.…”
mentioning
confidence: 85%
See 4 more Smart Citations
“…Example 1) H 1 semi-norm errors and convergence orders in space (𝜏 = 1/100,000). Lu et al[28] can also be observed. In addition, we can see that the fourth-order scheme (3.26)-(3.31) can reduce the storage and computational cost significantly.…”
mentioning
confidence: 85%
“…The global convergence order of this scheme in the H 1 semi-norm was proved to be O(𝜏 2 + h 2 ) in Lu et al [28]. Denote…”
Section: Numerical Examplesmentioning
confidence: 97%
See 3 more Smart Citations